Effect of Alveolar Ridge Preservation after Tooth Extraction: A Systematic Review and Meta-analysis. (October 2014) - Avila-Ortiz, G.; Elangovan, S.; Kramer, K.W.O.; Blanchette, D.; Dawson, D.V.
Alveolar ridge preservation strategies are indicated to minimize the loss of ridge volume that typically follows tooth extraction. The aim of this systematic review was to determine the effect that socket filling with a bone grafting material has on the prevention of postextraction alveolar ridge volume loss as compared with tooth extraction alone in nonmolar teeth. Five electronic databases were searched to identify randomized clinical trials that fulfilled the eligibility criteria. Literature screening and article selection were conducted by 3 independent reviewers, while data extraction was performed by 2 independent reviewers. Outcome measures were mean horizontal ridge changes (buccolingual) and vertical ridge changes (midbuccal, midlingual, mesial, and distal). The influence of several variables of interest ( i.e ., flap elevation, membrane usage, and type of bone substitute employed) on the outcomes of ridge preservation therapy was explored via subgroup analyses. We found that alveolar ridge preservation is effective in limiting physiologic ridge reduction as compared with tooth extraction alone. The clinical magnitude of the effect was 1.89 mm (95% confidence interval [CI]: 1.41, 2.36; p < .001) in terms of buccolingual width, 2.07 mm (95% CI: 1.03, 3.12; p < .001) for midbuccal height, 1.18 mm (95% CI: 0.17, 2.19; p = .022) for midlingual height, 0.48 mm (95% CI: 0.18, 0.79; p = .002) for mesial height, and 0.24 mm (95% CI: –0.05, 0.53; p = .102) for distal height changes. Subgroup analyses revealed that flap elevation, the usage of a membrane, and the application of a xenograft or an allograft are associated with superior outcomes, particularly on midbuccal and midlingual height preservation.